Optimasi Dan Desain Pemenuhan Ruang Parkir Institut Teknologi Garut - Ervitha Nur Kholly; Ida Farida (Jurnal Konstruksi, 2026)
The Garut Institute of Technology (ITG) is a higher education institution in Garut Regency that has experienced an 11% increase in student enrollment over the past five years. This growth requires improved infrastructure management, particularly in parking facilities, which are essential for students, lecturers, and staff. Proper planning is necessary to optimize the use of parking spaces. This study aims to design parking patterns and layouts at ITG based on the 1998 Technical Guidelines for Parking Facilities by the Directorate General of Land Transportation and the 2023 Technical Guidelines for Pedestrian Facilities No. 07/P/BM/2023. Currently, the lack of organized parking management at ITG has resulted in vehicles being parked haphazardly, causing congestion. The research uses a quantitative approach combined with participatory ergonomics. The planning results indicate varying space requirements with different angles and capacities for each area. Area 1, with a 45º angle, accommodates 89 motorcycles; Area 2, also with a 45º angle, accommodates 104 motorcycles; Area 3, with a 60º angle, accommodates 70 motorcycles; and Area 4, with a 60º angle, accommodates 91 motorcycles. Meanwhile, Area 5 is designed with a 90º angle for 8 passenger cars and a 45º angle for 125 motorcycles, while Area 6 uses a 180º layout accommodating 6 passenger cars. In total, the planned parking capacity provides 487 spaces for motorcycles and 14 spaces for passenger cars. This results in a 91% availability rate compared to the actual need. These findings are expected to help ITG reduce vehicle congestion and create a more orderly, efficient parking system in line with applicable technical standards.